Variations in Velopharyngeal Structure in Adults With Repaired Cleft Palate. (November 2018) - Perry, Jamie L.; Kotlarek, Katelyn J.; Sutton, Bradley P.; Kuehn, David P.; Jaskolka, Michael S.; Fang, Xiangming; Point, Stuart W; Rauccio, Frank
Objective: The purpose of this study was to examine differences in velopharyngeal structures between adults with repaired cleft palate and normal resonance and adults without cleft palate. Design: Thirty-six English-speaking adults, including 6 adults (2 males and 4 females) with repaired cleft palate (M = 32.5 years of age, SD = 17.4 years) and 30 adults (15 males and 15 females) without cleft palate (M = 23.3 years of age, SD = 4.1 years), participated in the study. Fourteen velopharyngeal measures were obtained on magnetic resonance images and compared between groups (cleft and noncleft). Results: After adjusting for body size and sex effects, there was a statistically significant difference between groups for 10 out of the 14 velopharyngeal measures. Compared to those without cleft palate, participants with repaired cleft palate had a significantly shorter hard palate height and length, shorter levator muscle length, shorter intravelar segment, more acute levator angles of origin, shorter and thinner velum, and greater pharyngeal depth. Conclusion: Although significant differences were evident in the cleft palate group, individuals displayed normal resonance. These findings suggest that a wide variability in velopharyngeal anatomy can occur in the presence of normal resonance, particularly for those with repaired cleft palate. Future research is needed to understand how anatomic variability impacts function, such as during speech.